BELAJAR MATEMATIKA SEKOLAH DASAR MELALUI TEKS CERITA NARATIF DI MASA PANDEMI COVID-19 - I Komang Sesara Ariyana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Learning mathematics in the midst of the Covid-19 pandemic has become more difficult than before. Learning mathematics is not enough just to give routine questions to count algorithmically. Certain strategies are needed in presenting mathematics learning, such as giving story questions. Story questions can be divided into routine questions and non-routine questions. Both types of story questions can be developed by incorporating adverbs of time, so that narrative story questions are formed. So from this narrative story problem also develops students' language skills. Language skills are also needed in understanding math problems. With narrative story questions, students' thinking can be directed according to the plot of the story presented. In addition, students can also be given assignments, namely posing problems in the form of simple narrative story questions that are initiated by a stimulus from the teacher. As a accompaniment impact, narrative text writing skills can also be developed.